DEVELOPMENT AND OPTIMIZATION OF IMMEDIATE RELEASE TABLET OF FEBUXOSTAT IN GOUT TREATMENT - PATEL, HITESHKUMAR RANCHHODBHAI (Asian Journal of Pharmaceutical Research and Development, 2018)
The Formulated Immediate Release tablet based was established by wet granulation techniques. The Optimized tablet were film coated for taste masking of unpleasant taste of Febuxostat drug to improve its patient compliance. The tablets were evaluated for pharmacopoeial and non pharmacopoeial (industry specified) tests. Based on the results, formulation F4 having optimized concentration of crosscarmellose sodium was identified as better formulation among all formulations developed for immediate release tablets. F4 Decrease in binder quantity and increase in disintegrant quantity and remaining all physical parameters of tablets were found satisfactory. Flow of blend was good. Disintegration time and dissolution found comparable to the reference product. Uniformity of dosage units found satisfactory. Further optimization had done by 10 more batches using different concentration of diluents, binders, lubricant, disintegrating agent & glidant and final batches was selected. The result arrived in this work indicates the immediate release formulation of Febuxostat developed in this work was found to be equivalent to reference product, based on the in-vitro Release studies and other evaluation parameters envisaged the objectives of work.